Multi-dimensional pinch analysis for sustainable power generation sector planning in China - Jia, Xiaoping (Animo Repository, 2016)
© 2015 Elsevier Ltd. All rights reserved. Emerging economies account for a fast-growing share of the global energy market. In particular, energy use in China has become significant from both economic and environmental standpoints. This trend makes it necessary to balance the need for affordable, reliable electricity supply with the need to ensure that the power infrastructure is environmentally sustainable. As such, this paper presents a multidimensional pinch analysis (MDPA) of the power generation sector in China; the analysis considers five key indices: carbon footprint, energy return on investment (EROI), water footprint, land footprint, and risk to humans. By simultaneously quantifying five different indices under a common methodological framework, we are able to coherently assess the impact on five different environmental concerns. This approach provides a more complete picture of the true environmental impact of China's power sector. This information can thus help policymakers avoid the problem of shifting environmental impacts to other domains, which can occur when the analytic procedure used focuses on a single environmental dimension.